Mini SBAR Implementation Training in Handovers as an Effort to Improve Patient Safety in Inpatient Rooms - Khairunnisa Batubara; Rinawati; Elvipson Sinaga; Irwan Agustian; Romauli Ervanny Goria Siallagan; Rahmat Ali Putra Harahap (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
One important measure of the quality of hospital services is patient safety. The efficiency of communication during the nurses' handover procedure is one element affecting patient safety. Misinformation can result from unstructured communication, which affects patient safety. Therefore, by using Mini SBAR (Situation, Background, Assessment, Recommendation), efforts must be made to increase nurses' proficiency in systematic communication. The purpose of this community service project is to enhance nurses' comprehension and proficiency in using Mini SBAR in the inpatient ward handover procedure. Training through counseling, demonstrations, and simulations of the usage of Mini SBAR in handover was the approach employed in this exercise. 56 nurses who worked in inpatient wards across four hospitals participated in the activity. After the training, participants' abilities were observed and their knowledge was measured as part of the evaluation process. The activity's outcomes demonstrated an improvement in nurses' comprehension and proficiency with Mini SBAR handover communication. Participants were able to communicate patient information in a more organized, methodical, and unambiguous manner, which reduced nurses' communication errors. Patient safety in inpatient wards has increased as a result of this training's successful improvement of clinical communication quality.